Potencialidade do uso de bactérias secretoras de enzimas digestivas no cultivo do tambaqui Colossoma macropomum (Cuvier, 1818) - Machado, Michel Lopes (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Aquaculture in Amazonas state is increasing at a very high ratio in the last few years, and the tambaqui is the main cultured specie. Feeding may represent up to 60% of the final producing costs. A research area increasing rapidly in aquaculture is on the development and use of probiotics, microorganisms living in the gastrintestinal tract that may have benneficial effects to the host. Isolation and enumeration of bacterial microbiota have been carried out, and the best protease extracellular producers were tested to be incorporated in fish diets. Amylolytic, lipolytic and proteolytic activities have been screened, and viable count of the enzyme producing were 1,31 x 108, 1,82 x 108 and 1,27 x 108 UFC/g digestive tract, respectively, with four, 29 and 46 extracellular producers. Within the 46 extracellular protease producers, six of them have exhibited higher activity than two UA, 32 have exhibited activity between one and two UA and eight had activity lower than one UA. Isolates TP1, TP20 e T3P18 have been considered not pathogen, and the incorporation process to diet has been evaluated. Pure cultures of these strains have been selected for morphological and biochemical characterization. On the basis of these tests, the isolate TP1 was identified as Micrococcus sp. and the others to genus Bacillus sp. We observed a decaying of 102 viable counts in the experimental diet tested during the process. There is a distinct microbial source of digestive enzymes (amylase, lipase and protease) apart from the endogenous sources in tambaqui gastrointestinal tract. The extracellular protease producing bacteria kept viable after incorporation process.